BlindMobi: A system for bus identification, based on Bluetooth Low Energy, for people with visual impairment - de Andrade, Hilson G. V.; Borges, David de M.; Bernardes, Leandro H. C.; de Albuquerque, João Lucas A.; da Silva-Filho, Abel G. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2019)
This paper presents a bus detection system based on Bluetooth low energy (BLE) technology that aims to ease the traveling of blind people, in large urban centers. The proposed system consists of two subsystems: one embedded hardware on the buses and the other running on the user mobile device. From the device embedded on the bus, BLE beacons containing itinerary information and bus acceleration are sent and read by the application running on the mobile device. Through this information and using the machine learning algorithm, the application is able to identify the approach and arrival of the bus, guiding the user. A complete system prototype has been constructed and tested to validated the proposed system, where a rating rate of 91.5% was obtained, indicating the feasibility of the proposal.